Forensic Research Progress on Bongkrekic Acid Poisoning - CHEN Xuan-long; YUAN Qiang; SUN Yong; ZHANG Die; FU Jian-bin; LI Li-liang (Fayixue Zazhi)
Bongkrekic acid （BA） is a toxin with stable properties and no distinctive smell. It exists in common foods such as fermented edible grain products, potato products, spoiled tremella fuciformis and auricularia polytricha, as well as auricularia polytricha that has been soaked too long. It can easily cause food poisoning. At present, there is still a lack of complete method to detect BA, and no specific antidote of BA has been found. Therefore, BA poisoning is easy to be misdiagnosed or missed diagnosed, and its mortality rate remains high. In recent years, studies have revealed the toxic mechanism of BA and found that BA can inactivate some enzymes containing thiol groups （-SH） and inhibit the synthesis and transport of adenosine triphosphate （ATP）, causing damage to liver, kidney, brain and other parenchymal organs. This article reviews the autopsy cases and literature of deaths caused by BA poisoning at home and abroad, systematically summarizes the epidemiology, clinical manifestations, pathological changes, toxicological mechanisms, detection methods, forensic diagnostic key points and challenges of BA in forensic medicine, with the aim of providing a reference for forensic identification of related cases.